2014
DOI: 10.1007/s10964-014-0140-9
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Racism, Racial/Ethnic Attitudes, Motivated Fairness and Mental Health Outcomes Among Primary and Secondary School Students

Abstract: While studies investigating the health effects of racial discrimination for children and youth have examined a range of effect modifiers, to date, relationships between experiences of racial discrimination, student attitudes, and health outcomes remain unexplored. This study uniquely demonstrates the moderating effects of vicarious racism and motivated fairness on the association between direct experiences of racism and mental health outcomes, specifically depressive symptoms and loneliness, among primary and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
82
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(88 citation statements)
references
References 69 publications
2
82
0
4
Order By: Relevance
“…Australia schools are the most common setting in which children and adolescents experience racism (Mansouri et al, 2009;Priest et al, 2014), defined as behaviour and practices acting to generate avoidable and unfair treatment of groups of people because of their race, ethnicity, culture or religion (Berman & Paradies, 2010). Mansouri et al (2009) found that racist name-calling affected 38 per cent of respondents among high school students in Australia's east coast states and in the Northern Territory.…”
Section: Racismmentioning
confidence: 99%
“…Australia schools are the most common setting in which children and adolescents experience racism (Mansouri et al, 2009;Priest et al, 2014), defined as behaviour and practices acting to generate avoidable and unfair treatment of groups of people because of their race, ethnicity, culture or religion (Berman & Paradies, 2010). Mansouri et al (2009) found that racist name-calling affected 38 per cent of respondents among high school students in Australia's east coast states and in the Northern Territory.…”
Section: Racismmentioning
confidence: 99%
“…Kwate and Goodman (2015) call attention to methodological difficulty in proving the association between exposure to racism and the development of mental disorders with longitudinal section studies, which makes these studies expensive. However, the experience of racism has proven association with feelings of loneliness among young people (Priest et al, 2014), days of poor mental health (Kwate;Goodman, 2015) and symptoms of anxiety and depression (Pieterse et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies suggest that a substantial number of youth are treated badly and victimized due to their ethnic or cultural background at school (e.g., Bayram € Ozdemir & Stattin, 2014;Verkuyten & Thijs, 2002). Such negative experiences jeopardize the integration of immigrant adolescents into the host society (Marks, Ejesi, McCullough, & Garc ıa Coll, 2015) and have negative consequences for their psychological functioning, such as negative self-perception (Bayram € Ozdemir & Stattin, 2014), elevated anxiety, stress, and depressive symptoms (Hoglund & Hosan, 2013;McKenney, Pepler, Craig, & Connolly, 2006), and feelings of loneliness (Priest, Perry, Ferdinand, Paradies, & Kelaher, 2014).…”
mentioning
confidence: 99%